PENERAPAN URBAN FARMING DI DESA ROWOLAKU SEBAGAI UPAYA MENINGKATKAN KETAHANAN PANGAN - Anggraeni, Dewi; Neriza Apriani (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The economic shift from agriculture to trade and services due to the development of educational institutions has resulted in the decline of agricultural land and threatens local food security. To overcome this problem, an urban farming program was implemented by utilizing used plastic bottles as planting media to grow kale. Urban farming was chosen because it can overcome land limitations while reducing plastic waste. The service activities were carried out using a sercive leraning approach which began with coordination, continued with socialization, and hands-on practice of making planting media. Periodic reviews are carried out to monitor plant growth. Results The Urban farming program not only strengthens local food security but also provides solutions to environmental and economic problems by empowering the community through the appropriate use of land and waste. This program shows great potential in building food security and supporting environmental sustainability amid the challenges of rapid urbanization